Environmental literacy as incidental learning - Gordon, Joye (Kansas State University, 2009)
Incidental learning is unplanned, perhaps unintentional. In a senior-level public relations cases course, case studies and readings dealing with environmental issues were utilized along with out-of-class experiential learning activities. Statically significant changes were found for 9 out of 18 items on the pre-post environmental literacy instrument. For example, students were significantly more likely to disagree with the statement that the U.S. is a world leader advancing responsible environmental policy at the end of the semester. Moreover students reported they were more comfortable describing themselves as “environmentalists.” They were more likely to agree the scientific studies may be subject to bias and more likely to agree that coal-burning technologies pose threats to the environment. Such changes in attitudes were not overt course objectives but were incidental outcomes of the student’ immersion into understanding environmental issues through public relations cases and reading and their involvement in out-of-class experiential learning activities.
Keywords: Incidental learning; Scientific studies; Environmental literacy; Bias; Environmental issues; Coal-burning technologies